Why should our mind reading abilities be involved in the explanation of phenomenal consciousness? - Perez, Diana Ines (2008)
In this paper I consider recent discussions within the representationalist theories of phenomenal consciousness, in particular, the discussions between first order representationalism (FOR) and higher order representationalism (HOR). I aim to show that either there is only a terminological dispute between them or, if the discussion is not simply terminological, then HOR is based on a misunderstanding of the phenomena that a theory of phenomenal consciousness should explain. First, I argue that we can defend first order representationalism from Carruthers' attacks and ignore higher order thoughts in our account of phenomenal consciousness. Then I offer a diagnostic of Carruthers' misunderstanding. In the last section I consider further reasons to include mindreading abilities in an explanation of phenomenal consciousness.